Cadets of Gascony: Two stories of old France - Stevenson, Burton Egbert, 1872-1962; Betts, Anna Whelan, 1875-1959 (Salt Lake City, UT : Project Gutenberg, 2022)
"Cadets of Gascony: Two Stories of Old France" by Burton Egbert Stevenson is a historical adventure novel written in the early 20th century. The book unfolds tales set against the backdrop of France, filled with themes of love and daring exploits. The narrative centers on a young protagonist, Paul de Marsan, who embarks on adventures involving romance, intrigue, and peril, particularly with a character named Claire who plays a significant role in his journey. The opening of the story introduces the reader to Marsan as he unexpectedly encounters a captivating young woman named Claire, who urgently seeks his help. Their fleeting yet intense interaction leads Paul into a dangerous situation, where he heroically intervenes to save a man from a cruel fate at the hands of masked villains. The action escalates as he finds himself drawn into a deeper conflict involving duels, a dark conspiracy, and the complexities of loyalty and honor. As the danger mounts, the stakes become clearer, setting the stage for the unfolding drama and adventure that promises a captivating blend of romance and heroic escapades throughout the book. (This is an automatically generated summary.)
Marsan -- A child of the night.
Release date is 2022-10-07
D A Alexander, David E. Brown, and the Online Distributed Proofreading Team at https://www.pgdp.net (This file was made using scans of public domain works put online by Harvard University Library's Open Collections Program.)
Keywords: Gascony (France) -- Fiction